EVALUATING THE EFFICACY OF COGNITIVE BEHAVIORAL THERAPY FOR AMPHETAMINE USE DISORDER: IMPACT OF SOCIO-DEMOGRAPHIC AND BEHAVIORAL FACTORS IN PAKISTAN - Hussain Azad, Abrar; Ijaz Ali,; Farhan Nazir,; Muhammad Usman Anjum,; Muhammad Ali Raza,; Ahmed Azeem Dar,; Shaaray Abrar Umar,; Pashma Wazir, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Worldwide there is a growing recognition of amphetamine use disorder (AUD) as a significant public health problem. There is high prevalence in Pakistan. In the category of most potent central nervous system stimulants, amphetamines carry the high risk of severe dependence and multiple adverse health consequences. The objective of this study is to provide evaluation of efficacy of CBT for AUD in Pakistani population and impact of sociodemographic and behavioral factors. Methods: A quasi-experimental design was applied with 100 participants recruited from outpatient treatment centers and rehabilitation centers in Pakistan. A culturally adapted CBT program was delivered to 50 participants along with treatment as usual and standard treatment as usual (TAU) was given to control group with 50 participants. Addiction Severity, anxiety, depression, psychological wellbeing, quality of life, as well as relapse rates were measured using pretest and posttest assessments. Descriptive statistics, paired t-tests, ANOVA, multiple regression and survival analysis were completed to analyze the data. Results: The frequency of amphetamine use from pre to post change from 5.8 to 2.3 days per week (p<0.001) and ASI, addiction severity index scores from pre to post change from 30.2 to 18.7 (p<0.001) was significant in the CBT group. On the behavioral as well as on the psychological measures, improvements were observed, as evidenced by a decrease in the BDI from 22.4 to 14.1 (p<0.001) and a decrease in the GAD-7 from 18.5 to 11.3 (p<0.001). Significantly higher Quality of Life (WHOQOL-BREF) scores improved from 45.3 to 62.0 (p<0.001). But the TAU group also got better, just not as much as the CBT group. Positive associations were found with socio-demographic factors (such as higher education, stable employment and strong family support) and negative associations with unemployment, longer duration of addiction and regular alcohol intake. Conclusions: Both the effectiveness of CBT and its suitability to reduce amphetamine use, enhance psychological wellbeing, and improve quality of life among individuals with AUD.